DESAIN DAN IMPLEMENTASI PERALATAN VACUUM STABILIZER MENGGUNAKAN PRINSIP BERNOULLI UNTUK MENINGKATKAN KINERJA ROTARRY DRUM VACUUM FILTER - Ferry Setiawan (Journal of Food Technology and Agroindustry dipublikasikan oleh Universitas Wiraraja, 2022)
The purpose of this research is to create and implement a Vacuum Stabilizer equipment design to improve the performance of Rottary Drum Vacuum equipment in the sugar industry in the dirty juice filtration process which so far has not been optimal, this is indicated by the results of dirty juice filtration resulting in cake (blotong). which still has a fairly high sucrose content with a cake pol number > 2.5%, while the allowable standard is < 2.5%. From the identification results, it was found that the cause of the problem was the achievement of high vacuum and low vacuum work parameters which were still fluctuating and tended to be low with a very fluctuating high vacuum at 30 CmHg to 40 CmHg and Low Vacuum at 5 CmHg to 15 CmHg. The planned Vacuum Stabilizer equipment consists of a series of equipment such as reservoir tanks, venturi tanks and pipelines whose height is calculated by the bernoulli equation. The height of the Vacuum Stabilizer equipment, for high vacuum was achieved at a total height of 4.3 meters, while for low vacuum a total height of 3.9 meters, the Vacuum Stabilizer equipment succeeded in increasing the stability of achieving high vacuum at 45 CmHg – 55 CmHg and low vacuum at 20 CmHg. – 25 CmHg according to the standard set, with the impact of increasing performance so that the cake pol number matches the target set with the cake pol number < 2.5%.